COMPARING THE USE OF FIVE-PACKAGE OF MATH IN THE 2011 NATIONAL EXAMINATION BETWEEN SMA AND MADRASAH ALIYAH: A CASE STUDY IN JAKARTA - Wardani Rahayu (Program Pascasarjana Universitas Negeri Jakarta, 2014)
This study aims to compare five question packages used in the 2011 National Examination, specifically for Maths for Social Studies subject between public senior high school (SMA) and Islamic senior high school (MA) in Jakarta. It employed simple random sampling as its data collection technique. The independent variables used were the category of high schools and the Five Question Packages used in the National Examination. The schools were divided into two: regular senior high school (SMA) and Islamic senior high school or Madrasah Aliyah (MA). The packages chosen to be analyzed were package number: 12, 25, 39, 46 and 54. The data was analyzed by two-factor ANOVA for its 11 Differential Item Function (DIF) and 29 non Differential Item Function (non-DIF) items. The items used for this study are the items that fit the three-parameter logistic model. This study found that no difference between the scores on both the DIF and non-DIF items in either for SMA or Ma is found. Keywords: national examination in math, five packages, DIF, SMA, MA.